Spray-Drying Synthesis of LiFeBO3/C Hollow Spheres With Improved Electrochemical and Storage Performances for Li-Ion Batteries - Sui, Yulei; Chen, Wei; Tang, Shibao; Wu, Ling; Wang, Binjue; Li, Huacheng; Li, Wei; Zhong, Shengkui (Frontiers in Chemistry, 2019)
LiFeBO3/C cathode material with hollow sphere architecture is successfully synthesized by a spray-drying method. SEM and TEM results demonstrate that the micro-sized LiFeBO3/C hollow spheres consist of LiFeBO3@C particles and the average size of LiFeBO3@C particles is around 50-100 nm. The thickness of the amorphous carbon layer which is coated on the surface of LiFeBO3 nanoparticles is about 2.5 nm. LiFeBO3@C particles are connected by carbon layers and formed conductive network in the LiFeBO3/C hollow spheres, leading to improved electrical conductivity. Meanwhile, the hollow structure boosts the Li+ diffusion and the carbon layers of LiFeBO3@C particles protect LiFeBO3 from moisture corrosion. Consequently, synthesized LiFeBO3/C sample exhibits good electrochemical properties and storage performance.